Behavioral Theory and Organizational Culture: The Interplay of Transformational Leadership, Team Dynamics, and Motivation in Driving Change at Tridinanti University of Palembang - Irayani, Irayani; Melvani, Frecilia Nanda; Azrin, Amrillah; Mikial, Msy. (The Eastasouth Management and Business, 2025)
This research investigates the impact of behavioral theory on organizational culture at Tridinanti University of Palembang, focusing on the roles of transformational leadership, team dynamics, and employee motivation in driving cultural change. Behavioral theory offers a framework for understanding how psychological and social factors shape individual behaviors within organizations, ultimately influencing the overall culture. At Tridinanti University, transformational leadership plays a critical role in aligning the university's vision with the efforts of staff and faculty, inspiring them to exceed performance expectations and embrace new initiatives. In conjunction with leadership, positive team dynamics contribute to effective collaboration, trust, and communication, creating a supportive environment for innovation and change. Employee motivation, both intrinsic and extrinsic, further strengthens this relationship by ensuring that staff members are engaged, proactive, and committed to the university's success. The purpose of this study is to explore the interplay between these three key factors and how they collectively influence the cultural transformation process within the university. Through qualitative methods, this research analyzes the experiences of leaders, teams, and employees, providing insights into how organizations can foster a culture that supports adaptability, innovation, and continuous improvement. The findings suggest that transformational leadership, when combined with strong team dynamics and high employee motivation, serves as a catalyst for developing an organizational culture that is resilient and forward-thinking. The implications of this study offer practical recommendations for higher education institutions seeking to create and sustain an organizational culture that promotes long-term growth and success. By leveraging the principles of behavioral theory, Tridinanti University and similar institutions can cultivate an environment that enhances both individual and collective contributions to institutional goals.